2018
DOI: 10.1297/cpe.27.145
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of daily recombinant human growth hormone treatment in Japanese short children born small for gestational age: final report from an open and multi-center study

Abstract: Abstract.Our study aimed at evaluating the safety and efficacy of GH treatment up to near adult height (NAH) for short children born small for gestational age (SGA). This was a multi-center, open-label, long-term extension study after a one-year, randomized, open-label, dose-response study. The primary objective was to assess safety, determined by adverse events and laboratory test parameters. Height parameters were evaluated as a secondary objective. The final data after all patients completed the study were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
24
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 22 publications
(27 reference statements)
9
24
2
3
Order By: Relevance
“…The lower mean IGF I SDS following initiation of GH treatment reported in our study when compared with those reported by Tanaka et al. ( 13 ) may reflect the under-dosing of GH and it is possible that higher doses of GH could have produced more pronounced improvements in height outcomes. There may also be differences in the IGF I response associated with GH treatment in children born SGA depending on the etiology of their condition and whether or not they are GH deficient ( 33 ).…”
Section: Discussioncontrasting
confidence: 57%
See 4 more Smart Citations
“…The lower mean IGF I SDS following initiation of GH treatment reported in our study when compared with those reported by Tanaka et al. ( 13 ) may reflect the under-dosing of GH and it is possible that higher doses of GH could have produced more pronounced improvements in height outcomes. There may also be differences in the IGF I response associated with GH treatment in children born SGA depending on the etiology of their condition and whether or not they are GH deficient ( 33 ).…”
Section: Discussioncontrasting
confidence: 57%
“…These data are reassuring and do not suggest an inappropriate increase in IGF I SDS. An increase in IGF I SDS to approximately +2 after the start of GH treatment was reported by Tanaka et al ( 13 ). The lower mean IGF I SDS following initiation of GH treatment reported in our study when compared with those reported by Tanaka et al.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations